Analisis Transparansi dan Akuntablitias Pengelolaan Dana Sekolah - Nurdiani, Mia Silmi; Nugraha, Nugraha (JURNAL PENDIDIKAN AKUNTANSI & KEUANGAN, 2018)
AbstractThis research was conducted at SMK Negeri 11 Bandung. The problem examined in this study is that there are still schools that tend to be not transparent in managing school funds. The objectives of this study were: 1) to find out how the school funds management was described, 2) to find out whether the school was transparent in managing school funds and 3) to find out whether the school was accountable in managing school funds. The research method used is descriptive method with a quantitative approach. Tool for collecting data about transparency and accountability with non-test techniques in the form of questionnaires and interviews. The data analysis technique uses descriptive analysis. The results showed that the transparency of fund management at SMK Negeri 11 Bandung showed a transparent category with a percentage of 81.95% of the management accountability of the funds showing an accountable category with a percentage of 85.04%. Keywords. transparency; accountability; school fund management AbstrakPenelitian ini dilakukan di SMK Negeri 11 Bandung. Masalah yang dikaji dalam penelitian ini adalah masih adanya sekolah yang cenderung tidak transparan dalam pengelolaan dana sekolah. Tujuan penelitian ini adalah: 1) untuk mengetahui bagaimana gambaran pengelolaan dana sekolah, 2) untuk mengetahui apakah sekolah telah transparan dalam pengelolaan dana sekolah dan 3) untuk mengetahui apakah sekolah telah akuntabel dalam pengelolaan dana sekolah. Metode penelitian yang digunakan adalah metode deskriptif dengan pendekatan kuantitatif. Alat pengumpulan data tentang transparansi dan akuntabilitas dengan teknik non tes dalam bentuk kuisioner dan wawancara. Teknik analisis data menggunakan analisis deskriptif. Hasil penelitian menunjukkan bahwa transparansi pengelolaan dana di SMK Negeri 11 Bandung menunjukkan kategori transparan dengan persentase 81,95% akuntabilitas pengelolaan dana menunjukkan kategori akuntabel dengan persentase 85,04%. Kata Kunci: transparansi; akuntabilitas; pengelolaan dana sekolah.